SISTEM KEARSIPAN ADMINISTRASI DESA BERBASIS WEB - Mokhamad Iklil Mustofa; Zaenal Mustofa (Universitas Muhammadiyah Semarang, 2018)
Internet network infrastructure is currently very rapid and is followed by the movement / mobilization of the community in fulfilling the needs of life and education (temporarily domiciled outside the city), as well as public awareness of the needs of village administrative requirements, such as family cards, identity cards, birth certificates, ownership letters land and other village administrations, so that the village apparatus must be extra in carrying out data collection on the village in an integrated manner, so that it can be accessed anywhere via an internet connection without returning to their hometown. Villagers who migrate outside the island want to make birth certificates, renew e-ID cards, family cards, etc., do not need to go back to their hometowns, just send physical and file-scanned files that are expected to be applied